Religious Harmony and Tolerance in Disruption Era: A Study of Local Wisdom in Watu Asa of Central Sumba - Suryaningsi Mila; Solfina Lija Kolambani (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2020)
Intolerance has been a major concern in religious life in the disruption era. This current study aims to discuss local wisdom that has helped maintain religious harmony and tolerance in Watu Asa of Central Sumba. The study was qualitative and descriptive in nature, while the investigation was carried out through participatory observation on the dynamics of religious life and in-depth interviews with religious and traditional leaders in Watu Asa Village. The results of the investigation confirm that the three religious communities, i.e. Christians, Marapu, and Muslims, can coexist peacefully because of the local wisdom and strong kinship. The local wisdom embedded in the tradition of tana nyuwu watu lissi, palomai or palonggamai, kalli kawana kalli kawinni, pandula wikki, mandara, and paoli, promotes the values of love, respect, mutual cooperation, and acceptance of one another. Those values are believed to be a social cohesion that interconnects interreligious people, regardless of their geographical, ethnic, and gender differences. Taken together, these results highlight the importance of the values of local wisdom as counter-narratives against intolerant religious ideology.